Effect of palladium and its nanogeometry on the redox electrochemistry of tetracyanoquinodimethane modified electrode; application in electrochemical sensing of ascorbic acid - Maurya K.K.; Singh K.; Malviya M. (My University, 2025)
The current work reports the effect of palladium nanoparticles and their nanogeometry on the redox electrochemistry of tetracyanoquinodimethane (TCNQ) modified electrodes. Palladium nanoparticles were prepared with different concentrations of 3-aminopropyltrimethoxysilane and calcination at 600 °C to yield PdNP-1 and PdNP-2 of the average size of 1 µm and 12 nm, respectively. The palladium nanoparticles were characterized by TEM, XRD, and AFM techniques. The electrochemical excellence of ascorbic acid was resoluted using cyclic voltammetry amperometry, electrochemical impedance spectroscopy, and differential pulse voltammetry. A limit of detection (LOD) was found to be 51.61, 44.38 and 30.10 µM over a linear range from 50 to 625 µM for modified CPE/TCNQ, CPE/TCNQ-PdNP-1, and CPE/TCNQ-PdNP-2, respectively, determined by amperometric analysis for ascorbic acid at pH 7. The synergistic effect of Palladium and π* orbital of TCNQ played an important role in the enhancement of the catalytic activity of the modified electrode. The modified electrode showed good sensitivity, stability, and reproducibility which was confirmed by cyclic voltammetry, and amperometric analysis. The charge transfer resistance value also indicated that the modified electrode hads good electrocatalytic activity. Graphical abstract: [Figure not available: see fulltext.]. © 2023, The Author(s), under exclusive licence to Springer Nature B.V.